(untitled) (International journal of medical sciences, 2026)
Inula helenium L. (elecampane) is an important medicinal plant, and pharmacological studies conducted on its roots are widely distributed worldwide, particularly in tropical and subtropical regions. Numerous data are available on its traditional use among local populations, including applications for wound healing, skin diseases, ophthalmic disorders, colic, gastric ulcers, diarrhea, dysentery, fever, gynecological diseases, sleep disorders, oral rinses, anti-inflammatory purposes, insecticidal uses, and others [1]. Phytochemical investigations have demonstrated that many of its components are bioactive due to the presence of a wide range of secondary metabolites, such as terpenoids, flavonoids, alkaloids, steroids, and chromene derivatives, which have been evaluated through in vitro, in vivo, or clinical studies [2]. Reported pharmacological activities include antimicrobial and anti-inflammatory effects, antispasmodic action, radioprotective effects against gamma irradiation, anticancer and free radical scavenging activities, antimalarial properties, and others. The data summarized herein are intended to support further research related to ethnopharmacology, natural product chemistry, and pharmaceutical sciences, as well as to assist researchers and practitioners in these fields [3].